EVALUATION OF ORGANOLEPTIC PROPERTIES OF SOFT DRINKS PREPARED FROM PLANT MATERIALS - Nishonov, Utkirali; Mominov, Ulugbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article discusses the indicators affecting the quality of soft drinks, namely appearance, transparency, color, aroma, taste, and the amount of sediment on the quality of the product. Methods for determining the organoleptic indicators of drinks according to GOST 28188-89 and GOST ISO 6658-2016, as well as their color indicators, are presented.